(untitled) (World Science, 2022)
We performed an experiment to determine the resistance impact on the engine performance resulted from the engine fuel system. Therefore we designed a tool for creating artificial resistance in the fuel pipe for determining resistance contamination in the fuel system. The artificial resistance between high pressure pump pipe and engine fuel filter was created in the field and laboratory then the diagnostic program EEM3 was used in the experiment. We tested the resistance by the pipe and decreased the pipe diameter of the fuel flow resistance from 8.5mm to 2.3 mm with 18 versions. As a result of the test, the basic indicators of the engine were changed when pipe diameter reached 6.5mm from 8.2 mm. The certain change on cyclic fuel supply occurred when the fuel flow increased and pipe diameter dropped. Moreover, the basic indicators of fuel consumption, torque and engine power were changed. It influences to the basic indicators due to the fuel filter contamination and regression of permeability proficiency then the engine will lose out the fuel.